1952
DOI: 10.2170/jjphysiol.3.36
|View full text |Cite
|
Sign up to set email alerts
|

The Spike-Like and the Slow Components in Root Potentials

Abstract: Many studies have been reported on the root potentials, since the publication of the first systematic research by Barron and Matthews (1). The essential points, however, namely the structural elements responsible for them and the mechanism of their production, remain still obscure. During the course of investigation on these, the present authors came upon an idea to divide both ventral and dorsal root potentials into two components. The experimental basis of this idea and its bearings on the problem concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1952
1952
1977
1977

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Iwata and Otani (12) analysed the ventral root potential into two components; the spike-like and the slow. Among them, the spike-like component should be interpreted as a result of an electrotonic spread of syn-aptic potentials set up in motoneurone somata, as assumed in the previous paper (12).…”
Section: Discussionmentioning
confidence: 97%
“…Iwata and Otani (12) analysed the ventral root potential into two components; the spike-like and the slow. Among them, the spike-like component should be interpreted as a result of an electrotonic spread of syn-aptic potentials set up in motoneurone somata, as assumed in the previous paper (12).…”
Section: Discussionmentioning
confidence: 97%
“…Besides the effect on the action potential, it was shown by Furukawa (8) that tetraethylammonium (TEA) ions had a conspicuous effect of augmenting reflex activities in the toad's spinal cord at a certain stage of their action (see also Iwata and Otani,10).…”
mentioning
confidence: 99%
“…Kolmodin & Skoglund (1953) found a VRP in such preparations 24 hr after dissection. Iwata & Otani (1952) suggested that in the DRP also there is a superposition of motoneurone effects, especially in its initial maximum part. This assumption does not seem very convincing in view of the present finding that the DRP is well preserved for days and may become even higher in the isolated preparations, at a time when the VRP has disappeared.…”
Section: Discussionmentioning
confidence: 99%